Intrathecal Injection of scAAV9–hIGF1 Prolongs the Survival of ALS Model Mice by Inhibiting the NF-kB Pathway. (15th June 2018) - Hu, HaoJie; Lin, HuiQian; Duan, WeiSong; Cui, Can; Li, ZhongYao; Liu, YaKun; Wang, Wan; Wen, Di; Wang, Ying; Li, ChunYan
Graphical abstract: Highlights: Overexpressing hIGF1 decreased MN loss and the glial response by inhibiting the inflammatory response in ALS mice. Knocking-down mIGF1 increased MN loss and the glial response by exacerbating the inflammatory response in ALS mice. Overexpressing hIGF1 protected MN by inhibiting the NF-κB signaling pathway and increased the life span of ALS mice. Abstract: Amyotrophic lateral sclerosis (ALS) is a chronic, fatal neurodegenerative disorder characterized by the progressive loss of upper and lower motor neurons. Currently, there is no effective drug for ALS. Recent studies in ALS model mice have shown that insulin-like growth factor-1 (IGF1) may be a promising therapeutic drug. We demonstrate that self-complementary adeno-associated virus serum type 9 encoding the human IGF1 (scAAV9–hIGF1) could significantly postpone the onset and slow down the progression of the disease owning to inhibiting the NF-κB signaling pathway. Furthermore, the results were supported by experiments in which the CRISPR/Cas9 system was used to knock-down IGF1 in ALS mice (mIGF1). Our data indicate that IGF1-mediated suppression of NF-κB activation in microglia is a novel molecular mechanism underlying MN death in ALS. It provides new insight into IGF1 and points toward novel therapeutic targets of IGF1 in ALS.